Graduate students mentoring undergraduate students' business innovation pitches. Issue 2 (July 2020) - Bendickson, Joshua S.; Madden, Laura; Matherne, Curtis F.
Abstract: Pitch competitions are commonplace throughout undergraduate and graduate entrepreneurship curricula. Although they are valuable exercises, advancements are available to further their usefulness and reach a wider audience. Accordingly, we developed an experiential learning exercise rooted in the tenets of corporate entrepreneurship that allows for greater collaboration, learning, and critical thinking. In the exercise, undergraduate student groups develop and present an innovative initiative, then are scored and mentored by MBA student groups prior to the final pitches. The benefits include improved student learning by undergraduate students from graduate student mentors as well as improved mentoring and leadership skills for graduate students through the practical and experiential process of helping undergraduate students improve their pitches. Highlights: Experiential learning exercises create opportunities for students to develop teamwork and critical thinking skills. We describe a pitch competition that provides for experiential learning and collaboration between undergraduate students. Graduate students serve as judges in an initial round and then mentor selected teams for final pitches. Practice iterations with graduate mentors ensure that final pitches to industry managers are well-rehearsed and focused. Feedback provided from both sets of students relays a positive and useful experiential leaning experience.